2017
DOI: 10.5811/westjem.2016.10.32042
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physician-in-Triage Model in the Management of Abdominal Pain in an Emergency Department Observation Unit

Abstract: IntroductionGiven the nationwide increase in emergency department (ED) visits it is of paramount importance for hospitals to find efficient ways to manage patient flow. The purpose of this study was to determine whether there is a significant difference in success rates, length of stay (LOS), and other demographic factors in two cohorts of patients admitted directly to an ED observation unit (EDOU) under an abdominal pain protocol by a physician in triage (bypassing the main ED) versus those admitted via the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…1 7 These units, often staffed with a midlevel practitioner and supervised by ED attending staff, were originally developed to monitor patients presenting with chest pain but low clinical probability of myocardial infarction, with the goal of using fewer resources than the analogous admission to a cardiac ICU. 8 Subsequent data have shown that EDOUs can reduce inpatient admission rate, length of stay, and cost for a wide variety of acute medical problems [9][10][11][12][13][14] and the Institute of Medicine has concluded that EDOUs can reduce unwarranted hospitalizations and improve institutional patient flow. 15 Despite this, few studies have evaluated EDOU protocols for acute neurological presentations.…”
Section: Discussionmentioning
confidence: 99%
“…1 7 These units, often staffed with a midlevel practitioner and supervised by ED attending staff, were originally developed to monitor patients presenting with chest pain but low clinical probability of myocardial infarction, with the goal of using fewer resources than the analogous admission to a cardiac ICU. 8 Subsequent data have shown that EDOUs can reduce inpatient admission rate, length of stay, and cost for a wide variety of acute medical problems [9][10][11][12][13][14] and the Institute of Medicine has concluded that EDOUs can reduce unwarranted hospitalizations and improve institutional patient flow. 15 Despite this, few studies have evaluated EDOU protocols for acute neurological presentations.…”
Section: Discussionmentioning
confidence: 99%
“…Nicht nur aufgrund des demographischen Wandels mit einem steigenden Anteil der älteren Bevölkerung [4,17], sondern auch aufgrund des vermehrten Patientenaufkommens in den Notaufnahmen [10,11] müssen die aktuellen Versorgungsstrukturen kritisch evaluiert werden. Die NA als intersektorale Schnittstelle muss stationären und ambulanten Qualitätsanforderungen gerecht werden, somit ist die einheitliche Qualitätsdokumentation und -messung in der Notfallmedizin anzustreben [8].…”
Section: Introductionunclassified